Baltic Cluster Report : Staff Report for the 2014 Cluster Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
This 2014 Cluster Consultation report examines common themes and challenges facing the three Baltic countries-Estonia, Latvia, and Lithuania. It identifies common features and common challenges, and discusses policies-both national and joint-that could help to address these challenges. The Baltic economies have performed well during the last two decades. The global financial crisis exposed vulnerabilities that had built up in the Baltics, but the postcrisis recovery revealed inherent strengths as well. This report highlights that national policies are necessary to address all of the challenges, but collaboration is also important in some areas.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet